Rural tourism in Bukovina in the face of SARS-COV-2 pandemic - Daniela Matei; Viorel Chiriţă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Tourism is one of the most vulnerable industries when facing a global threat of sanitary, economic, or military considerations. From an economic activity comprising nearly 3% of the country's GDP, the tourism has dropped to a flat zero in Romania. For three months, specifically March - May 2020, almost 97% of the accommodation units were closed, and only those hosting medical staff or quarantined persons were open during this period. The present study runs an analysis on the tourism in Bukovina during March-July 2020 and employs both quantitative and qualitative methods. The results have highlighted that tourists were partial to a certain type of accommodation units, namely agritourist and tourist guesthouses in Bukovina. Another visible fact is the predilection for remote places with good accessibility located along the main road axes to Bukovina (stopovers, tourist cottages, chalets, and campsites).
Keywords: Q26; Q54; Q56; Z32; 330; Tourism; Pandemic; SARS-CoV-2; Resilience; Bukovina